O ensino de ciências naturais para alunos com deficiência auditivos na escola Benvinda de Araújo Pontes - SILVA, Eduarda da Conceição Silva da (2024)
The present research sought to analyze the inclusion of deaf students in the Natural Sciences at the Benvinda de Araújo Pontes school, as well as how to present some considerations of the education of the hearing impaired in Brazil and currently; analyze the difficulties of the teacher and the interpreter of the School chosen for the development of the research, in the city of abaetetuba. And also to identify the challenges of these professionals in relation to the lesson planning, the practices of prejudice and the lack of training to work with these students. The methodology used in this research was the conducting a case study, aiming to highlight the teacher's experience and the interpreter in Natural Sciences in this process of inclusion of students deaf or hard of hearing. To carry out the research, use of semi-directed interview. The research showed that the head teacher and interpreters need to review their practices to offer an education with quality, because what they are offering is very far from what is desired in relation to the inclusion of the hearing impaired in the Science discipline. However, in the case of those interviewed here, there was a commitment to create strategies that could facilitate the educational process of students A possibility to carry out research on education in the inclusive aspect, allowed the understanding of how school inclusion occurs in the aspects theoretical, from the authors researched and, in what refers to the practical aspect, in the voices of teachers who portrayed their daily experiences in interviews given to the researcher responsible for this procedure.